Left Ventricle Outflow Obstruction by Reverse-Oriented Tricuspid Semilunar Valve-Like Endocardial Duplicatures - Kristína Mikuš-Kuracinová; Pavel Babál; Eliška Kubíková (Case Reports in Cardiology)
A 57-year-old female had a history of hypertension disease, and one year before her death, her ECG showed signs of left ventricle hypertrophy. She died with signs of heart failure with pulmonary edema development. At autopsy, there was left ventricle hypertrophy (wall thickness: 21 mm). In the left ventricle outflow channel, 15 mm below the aortic valve on the muscular wall, there were three white 1–1.5 mm thick membranous semilunar valve-like structures with the sizes of 9, 7, and 5 mm, with concavities opened into the left ventricle, reducing the outflow area by 21.5%. These structures were hanging on the regular muscular ventricular wall, without any visible fibrous anchoring structure and without formation of commissures, and were composed of fine collagen and elastic fibers. Gross anatomy as well as histological structure was different from the subaortic membrane. The reported accessory reverse-oriented tricuspid semilunar valve-like structure is an unusual finding of a structure in the left ventricular outflow tract, to which we could not find an analogy in the available literature.